Modulation of cell-associated plasminogen activator activity by cocultivation of a stem cell and its tumorigenic descendant. - Liu, H Y (1984)
The effect of the presence of one cell type on the plasminogen activator activity of another cell type was studied. The cell types, AC and D, were isolated from a rat neuroblastoma (I. Imada and N. Sueoka, Dev. Biol. 66:97-108, 1978). AC cells are stem cells capable of multipotential differentiation in vitro and have little or no cell-associated plasminogen activator activity. D cells are tumorigenic and have high levels of cell-associated plasminogen activator activity. When AC cells were cocultivated with D cells, the plasminogen activator activity of the D cells was dramatically inhibited. The presence of as few as 1,250 AC cells inhibited 70% of the plasminogen activator activity of 20,000 D cells, as determined by a highly quantitative assay. The amount of inhibition by AC cells was proportional to the number of AC cells present. At increasing numbers of AC cells and a constant number of D cells, the Vmax for the activation of plasminogen proportionately decreased and the Km remained constant, implying that AC cells did not alter the structure or concentration of plasminogen. Inhibition was not mediated by a soluble inhibitor secreted by AC cells. Rather, attachment of AC cells adjacent to D cells, i.e., cell-to-cell contact, seemed to be required for inhibition. The substratum-attached material of AC cells, that which remained on the microwell surface after removal of AC cells with EDTA, inhibited D cell plasminogen activator activity. If plasminogen activator activity is involved in metastasis, then regulation of the plasminogen activator activity of one cell type by another cell type may be involved in determining which cells in a tumor can metastasize and where secondary tumors can arise.